Midnight Bayou [compact disc, unabridged] - Roberts, Nora (Brilliance Audio, 2001)
While renovating an old mansion on the outskirts of New Orleans, Declan Fitzgerald begins seeing visions of days from a century past. Local legend has it that the house is haunted but he uncovers the reason for the strange sensations of terror and unbearable grief.